Merchant Attitudes Toward a Healthy Food Retailer Incentive Program in a Low-Income San Francisco Neighborhood - McDaniel, Patricia A. (Int Q Community Health Educ, 2018)
In low-income urban communities across the USA and globally, small stores frequently offer processed foods, sodas, alcohol and tobacco, but little access to healthy products. To help address this problem, the city of San Francisco created a healthy food retailer incentive program. Its success depends, in part, on retailers’ willingness to participate. Through in-person interviews, we explored attitudes toward the program among store owners or managers of 17 non-participating stores. Eleven merchants were uninterested in the program due to negative past experiences trying to sell healthier products, perceived lack of customer demand, and fears that meeting program requirements could hurt profits. Six merchants expressed interest, seeing demand for or opportunity in healthy foods, foreseeing few difficulties in meeting program requirements, and regarding the assistance offered as appealing. Other municipalities considering such interventions should consider merchants’ perspectives, and how best to challenge or capitalize on retailers’ previous experiences with selling healthy foods.